THE PRACTICE OF USING MULTIMEDIA TRAINING COURSES IN TEACHING COURSES OF SPECIALIZATION - Dmitry A. Suslov (Статистика и экономика, 2016)
The implementation of competence-based approach involves a wide use in the educational process of active and interactive forms of training; the article describes the experience of using multimedia training courses in the teaching specialization.